Pengaruh Model PBL Dengan Pendekatan Open-Ended Terhadap Kemampuan CPS Siswa SMA Ditinjau Dari Students’ Beliefs - Rasmina, Rasmina; Fahinu, Fahinu; Makkulau, Makkulau (Jurnal Pembelajaran Berpikir Matematika (Journal of Mathematics Thinking Learning), 2018)
Abstrak: Penelitian ini bertujuan untuk mengetahui perbedaan rata-rata peningkatan kemampuan CPS siswa yang diajar dengan model PBL dengan pendekatan Open-Ended dan model pembelajaran konvensional; mengetahui perbedaan peningkatan kemampuan CPS antara siswa yang diajar dengan model PBL dengan pendekatan Open-Ended dan model pembelajaran konvensional ditinjau dari Students’ Belief about Mathematics. Penelitian ini dilakukan pada siswa kelas XI IPA SMAS Kartika XX-2 Kendari. Pengambilan sampel menggunakan teknik purposive sampling. Data dianalisis dengan statistik inferensial. Hasil penelitian menunjukan bahwa secara signifikan rata-rata peningkatan kemampuan CPS siswa yang diajar dengan model PBL dengan pendekatan Open-Ended lebih tinggi dibandingkan siswa yang diajar dengan model pembelajaran konvensional; terdapat perbedaan peningkatan kemampuan CPS antara siswa yang diajar dengan model PBL dengan pendekatan Open-Ended dan model pembelajaran konvensional ditinjau dari Students’ Belief about Mathematics.Kata kunci: CPS, PBL, Students’ Belief about Mathematics.Abstract: This study aimed find out the difference in the average of improvement in the CPS ability of students who were taught under the PBL model with Open-Ended approach and conventional model of learning; find out the difference in the average of improvement in the CPS ability of students who were taught under the PBL model with Open-Ended approach and those who were taught under conventional model of learning, as viewed from the Student’s Beliefs about Mathematics. This research is conducted at students of class XI IPA at SMAS Kartika XX-2 in Kendari. Samples were determined using the purposive sampling technique. Data analyzed by using inferential statistics. Results showed that significantly the average increase in the ability of CPS students who are taught with PBL model with Open-Ended approach is higher than students who are taught with conventional learning model; there are differences in the ability of CPS among students who taught using PBL model with Open-Ended approach and conventional learning model from Students' Belief about Mathematics. Keywords: CPS, PBL, Students’ Belief about Mathematics.